Early renal impairment affects hormonal regulators of calcium and bone metabolism and Wnt signalling and the response to vitamin D supplementation in healthy older adults. Issue 229 (May 2023) - Christodoulou, Marilena; Aspray, Terence J.; Piec, Isabelle; Washbourne, Christopher; Tang, Jonathan C.Y.; Fraser, William D.; Schoenmakers, Inez; ,
Abstract: Bone and renal metabolism are regulated by common factors and there is extensive cross-talk between these organs (the 'renal-bone-axis'). Ageing is associated with physiological changes including reduced bone mass, renal function and tissue sensitivity to regulatory hormones, impacting the renal-bone axis. We aimed to investigate the influence of estimated Glomerular Filtration Rate (eGFR) on plasma concentrations of vitamin D metabolites, Wnt signalling and bone metabolism in a dose ranging vitamin D3 RCT (12, 000 IU, 24, 000 IU, 48, 000 IU/month for 1 year; n = 379, >70 y) with a baseline eGFR > 30 mL/min/1.73 m 2 . Participants were categorised on basis of eGFR (≥60 or mL/min/1.73 m 2 ) based on 5 commonly used algorithms for eGFR. Differences between eGFR categories were tested with ANCOVA. Before supplementation commenced, a lower eGFR was associated with significantly higher concentrations of c-terminal and intact Fibroblast Growth Factor-23 (cFGF23; iFGF23), intact Parathyroid Hormone (iPTH) and Sclerostin (SOST) and lower Klotho, 1, 25-dihydroxy Vitamin D (1, 25(OH)2 D) and Dickkopf-related Protein 1 (DKK1) concentrations. Differences between eGFR groups in 25-hydroxy Vitamin D (25(OH)D), 24, 25-dihydroxy Vitamin D (24, 25(OH)2 D) and iPTH were only detected with eGFR based on Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) and Modification in Diet for Renal Disease (MDRD-4) algorithms. Differences in Bone Mineral Density and Content (BMD; BMC) and bone turnover markers were detected only with Cockcroft-Gault (CG). Pre- and post- supplementation comparisons showed differences in the response to supplementation by eGFR group. Plasma 25(OH)D, 24, 25(OH)2 D, 1, 25(OH)2 D and DKK1 increased and iPTH and C-terminal telopeptide (CTX) decreased in both groups. Plasma iFGF23, bone specific alkaline phosphatase (BAP) and Procollagen 1 intact N-terminal Propeptide (PINP) increased and phosphate decreased only in the group with eGFR ≥ 60 mL/min/1.73 m 2 . Findings were largely consistent across all eGFR algorithms. Post-supplementation, cFGF23, iFGF23, iPTH and SOST remained significantly higher in the lower eGFR group. Plasma 1, 25(OH)2 D and Klotho did no longer differ between eGFR groups. This was found for all eGFR algorithms, with the exception of iPTH and iFGF23, which were not significantly different with eGFR based on CG. Differences in BMD and BMC were detected with CKD-EPI-creatinine and MDRD-4 but not GC. This study showed that even a moderate decline in eGFR is associated with alterations in vitamin D metabolism, Wnt signalling and bone turnover markers. Renal function influenced the response to vitamin D supplementation. Supplementation increased Vitamin D metabolites in the group with moderate renal impairment to concentrations comparable to those found in the group with normal renal function. However, although CTX decreased, an increase in bone formation markers was not found in the group with eGFR 60 mL/min/1.73 m 2 . In conclusion, vitamin D supplementation had beneficial effects on markers of the renal-bone axis in older people with both normal and impaired renal function. Highlights: Changes in vitamin D metabolism, PTH, FGF23 and Wnt signalling are found from early CKD (G3a and 3b). Vitamin D supplementation increased plasma 25(OH)D, cFGF23, DKK1 and decreased iPTH and CTX with normal function and early CKD. The response to Vitamin D supplementation on c-terminal and intact FGF23, SOST and PINP depended on eGFR.